Efficacy of Herbal Medicine in Hand Osteoarthritis: A Narrative Review - Aghili, Seyedeh M.; Sahebari, Maryam; Salari, Masoumeh; Noorabadi, Parisa (Current Rheumatology Reviews, 2024)
Objective: Osteoarthritis (OA) is one of the most prevalent joint disorders in the world that has placed an enormous economic and social burden on governments and healthcare sectors in many countries. Hand OA (HOA) is the most common peripheral arthritis, which is less investigated than knee and hip OA. Due to limited approved drug choices and adverse effects of long-term use of current regimens, we aimed to review the existing evidence that were used as oral herbal medicine to treat HOA.Methods: The PubMed database was searched for both observational and interventional studies that have investigated herbal medicine safety and efficacy in HOA, written in English and published between 2010 and 2022.Results: A total of 5 original articles fulfilled the inclusion criteria, and each article assessed a different herbal regimen. Overall, it seems desirable to add specific herbal treatments to the regimen of HOA patients, specifically in case of early stages of HOA.Conclusion: Currently, the need for a low-risk alternative treatment in HOA patients is felt more than ever. There are reliable references relating to the safety of Korean red ginseng, GCSB-5, XLGB, and GS-GCu in these patients, although their efficacy was limited. Additionally, herbs like curcumin and Boswellia serrata have positively affected patients with knee osteoarthritis. However, there is a lack of strong evidence supporting their effectiveness in hand osteoarthritis (HOA). This emphasizes the potential benefits that these herbs may have for HOA patients.
Keywords: healthcare